Examination of the Effect of Cropyear on the Yield Potential and Yield Stability of Winter Wheat Varieties - Ágoston, Tamás; Pepó, Péter (Acta Agraria Debreceniensis, 2005)
Variety selection is one of the most important, determinative elements of sustainable winter wheat production. Yield potential, and yield stability are the most important elements in the variety selection of winter wheat, but baking quality parameters play an important role, too.Several winter wheat varieties were tested for yield and yield stability on chernozem soil in the Hajdúság (in the eastern part of Hungary), in the 2001-2002-2003-2004 cropyears. The management factors were the same for all cropyears. 15 varieties in early the maturity group, 14 varieties in the middle maturity group and 4 varieties in the late maturity group were tested in the above mentioned cropyears. The climatic conditions were average in 2001, dry in 2002, extremely dry in 2003, and very favourable in 2004.We obtained 5298-6183 kgha-1 yield from early maturity varieties, 5683-6495 kgha-1 from middle, 5694-6031 kgha-1 from late ones in the average of four years. The cropyears had strong influence on the yields, even on chernozem soil, and were characterized by excellent water – and nutrient – husbandry. Averaging of cropyears and genotypes, we obtained 6984 kgha-1 in 2001 (average cropyear), 5452 kgha-1 in 2002 (dry cropyear), 3120 kgha-1 in 2003 (extremely dry cropyear) and 8400 kgha-1 in 2004 (optimum cropyear), respectively. The yield differences between the minimum and maximum yields were 885 kgha-1 in early varieties, 812 kgha-1 in middle and 337 kgha-1 in late maturity varieties, respectively. The varieties characterized by high yield potential and the varieties characterized by good yield stability were different, so in variety selection we have to take both genetic traits into consideration. There were positive, significant correlations among the yields of winter wheat varieties (early, middle, late), the temperature of spring months. (March-April), and the rainfall of spring months (March-April) (R2=0,703**-0,768** and R2=0,681**-0,749**, respectively). We found a high negative correlation between the temperature of early summer months (May-June) and the yields of wheat varieties (R2= -0,856**- -0,918**).According to the results of our experiment, it is very important to harmonize yield potential and yield stability in the variety selection of winter wheat.